At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Let's start by simplifying the given expression step by step:
[tex]\[ \frac{(2 g^5)^3}{(4 h^2)^3} \][/tex]
1. Simplify the numerator [tex]\((2 g^5)^3\)[/tex]:
To simplify [tex]\((2 g^5)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (2 g^5)^3 = 2^3 \cdot (g^5)^3 \][/tex]
Calculate each part:
[tex]\[ 2^3 = 8 \][/tex]
[tex]\[ (g^5)^3 = g^{5 \cdot 3} = g^{15} \][/tex]
Therefore,
[tex]\[ (2 g^5)^3 = 8 g^{15} \][/tex]
2. Simplify the denominator [tex]\((4 h^2)^3\)[/tex]:
To simplify [tex]\((4 h^2)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (4 h^2)^3 = 4^3 \cdot (h^2)^3 \][/tex]
Calculate each part:
[tex]\[ 4^3 = 64 \][/tex]
[tex]\[ (h^2)^3 = h^{2 \cdot 3} = h^6 \][/tex]
Therefore,
[tex]\[ (4 h^2)^3 = 64 h^6 \][/tex]
3. Combine the simplified numerator and denominator:
Now we can form the fraction with the simplified numerator and denominator:
[tex]\[ \frac{8 g^{15}}{64 h^6} \][/tex]
4. Simplify the fraction:
Divide the numerator and the denominator by their greatest common divisor, which is 8:
[tex]\[ \frac{8 g^{15}}{64 h^6} = \frac{8}{64} \cdot \frac{g^{15}}{h^6} = \frac{1}{8} \cdot \frac{g^{15}}{h^6} = \frac{g^{15}}{8 h^6} \][/tex]
Hence, the expression [tex]\(\frac{(2 g^5)^3}{(4 h^2)^3}\)[/tex] simplifies to:
[tex]\[ \frac{g^{15}}{8 h^6} \][/tex]
So, the equivalent expression is [tex]\(\boxed{\frac{g^{15}}{8 h^6}}\)[/tex].
[tex]\[ \frac{(2 g^5)^3}{(4 h^2)^3} \][/tex]
1. Simplify the numerator [tex]\((2 g^5)^3\)[/tex]:
To simplify [tex]\((2 g^5)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (2 g^5)^3 = 2^3 \cdot (g^5)^3 \][/tex]
Calculate each part:
[tex]\[ 2^3 = 8 \][/tex]
[tex]\[ (g^5)^3 = g^{5 \cdot 3} = g^{15} \][/tex]
Therefore,
[tex]\[ (2 g^5)^3 = 8 g^{15} \][/tex]
2. Simplify the denominator [tex]\((4 h^2)^3\)[/tex]:
To simplify [tex]\((4 h^2)^3\)[/tex], apply the power of a product rule [tex]\((a \cdot b)^n = a^n \cdot b^n\)[/tex]:
[tex]\[ (4 h^2)^3 = 4^3 \cdot (h^2)^3 \][/tex]
Calculate each part:
[tex]\[ 4^3 = 64 \][/tex]
[tex]\[ (h^2)^3 = h^{2 \cdot 3} = h^6 \][/tex]
Therefore,
[tex]\[ (4 h^2)^3 = 64 h^6 \][/tex]
3. Combine the simplified numerator and denominator:
Now we can form the fraction with the simplified numerator and denominator:
[tex]\[ \frac{8 g^{15}}{64 h^6} \][/tex]
4. Simplify the fraction:
Divide the numerator and the denominator by their greatest common divisor, which is 8:
[tex]\[ \frac{8 g^{15}}{64 h^6} = \frac{8}{64} \cdot \frac{g^{15}}{h^6} = \frac{1}{8} \cdot \frac{g^{15}}{h^6} = \frac{g^{15}}{8 h^6} \][/tex]
Hence, the expression [tex]\(\frac{(2 g^5)^3}{(4 h^2)^3}\)[/tex] simplifies to:
[tex]\[ \frac{g^{15}}{8 h^6} \][/tex]
So, the equivalent expression is [tex]\(\boxed{\frac{g^{15}}{8 h^6}}\)[/tex].
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.